Ancillary justice - Leckie, Ann (Leckie, Ann. Imperial Radch series, 2014)
Now isolated in a single frail human body, Breq, an artificial intelligence that used to control a massive starship and its crew of soldiers, tries to adjust to her new humanity while seeking vengeance and answers to her questions.